IMPLEMENTATION OF DISCIPLINARY CHARACTER EDUCATION IN ELEMENTARY SCHOOLS - Alonso Geonyzl (Sensei International Journal of Education and Linguistic, 2021)
This study aims to explore, examine, and describe the implementation of disciplinary character education in and it is hoped that policies that support the success of character education can be found. This research is a qualitative approach. The research was conducted with the subject of school principals, teachers and students. Data was collected through observation, interviews and documentation. The technique of checking the validity of the data used is the triangulation technique. The results of the study show that implementing disciplined character education is carried out through nine policies, namely (1) creating a character education program; (2) establish school rules and class rules; (3) performing Dhuha and Dhuhur prayers in congregation; (4) create affective posts in each class; (5) monitoring students' disciplinary behavior at home through daily activity logbooks; (6) giving affective messages in various corners of the school; (7) involving parents; (8) involving the school committee and (9) creating a conducive classroom climate.